PREVALENCE OF PHOMOPSIS BLIGHT AND FRUIT ROT OF BRINJAL IN KASHMIR (Applied Biological Research, 2023)
The present study was aimed to assess the status of Phomopsis blight and fruit  rot, caused by Phomopsis vexans, in Kashmir (India), for which 27 sites in 3  districts (Bandipora, Baramulla and Ganderbal) were selected. The mean of  three fields represented disease incidence and intensity of respective site. Nine plants each from 4 corners and centre of each field were randomly selected and their leaves, stem and fruits examined for disease incidence and intensity. The  overall mean incidence and intensity of leaf blight, fruit rot and stemblightwere 48.1 and15.1%, 41.7 and18.4%, and21.4 and 6.2%, respectively. The maximum  disease incidence and intensity on leaves, fruit and stem were 64.4 and 22.2%,  55.2 and27.6%, and31.8 and10.1%, respectively, observedindistrictBaramulla.  The minimum disease incidence and intensity on leaves (30.9 and 8.2%,), fruits  (27.8 and 9.9%) and stem (12.9 and 3.1%) were observed in district Ganderbal.
Keywords: Brinjal; fruit rot; incidence; intensity; Phomopsis blight